0256 Influence of Likely Nocturnal Wakefulness on 24-Hour Patterns of Violent Crime in Adults and Juveniles. (12th April 2019) - Oliviér, Kayla; Perlis, Michael L; Troxel, Wendy; Basner, Mathias; Chakravorty, Subhajit; Tubbs, Andrew; Owens, Judith; Jean-Louis, Girardin; Killgore, William D S; Warlick, Chloe; Alfonso-Miller, Pamela; Grandner, Michael A
Abstract: Introduction: Being awake at night is associated with cognitive/affective dysregulation. Recently, it was found that nocturnal wakefulness is also a risk factor for completed suicide (self-harm). The present analysis examines whether nocturnal wakefulness is also a risk factor for violent crime (harm to others). Methods: Data were obtained from the National Archive of Criminal Justice Data and included rates of murder, violent sexual assault, robbery, aggravated assault, and simple assault across each hour of the day in 2016. These data were aggregated from law enforcement agencies in 38 states and Washington DC. Data were examined separately for adults (>18) and juveniles (<18). Standardized Incidence Ratios (SIRs) were computed to evaluate the proportion of violent crimes committed at each hour, relative to what would be expected given the proportion of the population awake at each hour (determined from normative values obtained from the American Time Use Survey). Results: Without adjustment for likelihood of being awake, violent crime peaks at 7-10pm in juveniles and 2-4pm among adults. This pattern changed after adjustment, revealing increased likelihood at night. For adults, more violent crime than would be expected by chance was observed at 23:00 (SIR=1.56), 0:00 (SIR=2.44), 1:00 (SIR=2.97), and 2:00 (SIR=2.86), and also 15:00 (SIR=1.43). For juveniles, more violent crime than would be expected by chance was observed at 22:00 (SIR=1.84), 23:00 (SIR=3.14), 0:00 (SIR=5.71), 1:00 (SIR=8.69), 2:00 (SIR=10.33), 3:00 (SIR=8.04), 4:00 (SIR=2.87). Conclusion: For adults, more violent crimes than expected occurred at night, peaking around 1-2am. For juveniles, there was also an elevated likelihood of crimes at night, peaking slightly later (2-3am). This is in contrast to unweighted crime statistics, which show peaks in the early afternoon in adults and early evening for juveniles. These data lend further credibility to the concept that there may be a biological vulnerability to cognitive/affective dysfunction when awake at night. Support (If Any): R01MD011600